Adaptation and validation of the Turkish version of the vaccine hesitancy 5 point Likert Scale - Kübra Temel Aslan; Pınar Ay; Dilara Kaş; Furkan Tosun; İrem Yürükcü; Emre Kekeç; Muhammet Furkan Şahin; Çiğdem Apaydın Kaya (Taylor & Francis Group, 2021)
The decrease in vaccine acceptance has been recognized as an emerging public health problem and there is therefore a need for reliable and validated tools that identify vaccine hesitancy. The objective of this study was to adapt and validate the Turkish version of the Vaccine Hesitancy 5-point Likert Scale which was originally developed by the WHO Strategic Advisory Group of Experts on Immunization. The study was carried out in a Family Health Center (FHC) in Istanbul over the period June 1-November 30, 2020. The participants were parents who had applied to the FHC for well-child visits and had a child ≤18 months of age. After the process of translation and back-translation, the Turkish version was pilot-tested, and its test-retest reliability was evaluated among 40 parents at a two-week interval. The validation was carried out with 306 parents through exploratory factor analysis. There was no statistical difference between the test-retest scores (p = .17). The intraclass correlation coefficient was 0.98 (p < .001). Cronbach's alpha coefficient was 0.81. Factor analysis yielded two subscales that were named "confidence' and 'risk perception" and explained 63% of total variance. Our results suggest that the Turkish version of the Vaccine Hesitancy 5-point Likert Scale is a reliable and valid instrument.